Mesenchymal Stem Cell Therapy to Reduce the Neurological Deficit of Chronic Ischemic Stroke Patients: A Systematic Review - nita, surya; Narwanto, Muhammad Ihwan; Yuli Hermansyah; Cholis Abrori; Novan Krisno Adji (Faculty of Medicine, University of Jember, 2024)
Current ischemic and hemorrhagic stroke treatments are limited by a narrow golden period and lack of regenerative benefits, so stem cell therapy emerges as an ideal candidate for functional recovery in stroke patients. Stem cell therapy, still being studied, is expected to repair ischemic areas damaged by stroke to restore their physiological functions and reduce neurological deficits in chronic stroke patients. This study aimed to determine the therapeutic efficacy of MSCs in reducing neurological deficits in chronic ischemic stroke patients. We conducted a systematic review. We searched PubMed, Cochrane Library, Science Direct, and Springer Link from inception until December 2022 for cohort studies dealing with mesenchymal stem cell therapy for patients with ischemic stroke. The citation-searching method in this study collected 1,038 articles using the advanced searching method and 8 articles using the citation-searching method, bringing the total number of articles to 1,046. The exclusion criteria used were articles with systematic reviews and meta-analyses and articles that were not accessible in full text. Based on the results of a systematic review study conducted, the conclusion that can be drawn is that MSCs therapy has proven effective in reducing neurological deficits in chronic ischemic stroke patients in terms of the decreased NIHSS score.